MUSE: Looking for life on Earth - Penny, A; Davis, G; Calcutt, S; Drummond, JR; Naylor, D; Seager, S (2001)
Future missions to measure the mid-infrared spectra of extrasolar planets will obtain spectra spatially integrated over the visible hemisphere of the planet. Interpretation of these spectra will be difficult because they will depend on several imponderable factors; the axial inclination of the planet to the line of sight, the illumination of the planet by its parent star, and the planets' season and climatic state. The spectra will also contain variable components due to changing clouds, planetary rotation and the presence of large satellites. In order to interpret better such spectra, and to constrain the design of missions to measure them, a study is underway of a dedicated mission to take spectra of the spatially-unresolved Earth and to quantify the dependence of the spectrum on these variables.